Comparative analysis of geothermal binary ORC systems: performance and environmental considerations for CO2 andwater as geofluids - Nkemakolam Chinedu Izuwa; Stanley Toochukwu Ekwueme; Ndubuisi Uchechukwu Okereke; Onyebuchi Ivan Nwanwe; Nnaemeka Princewill Ohia (Zaštita Materijala)
This study considers the process simulation of geothermal binary Organic Rankine Cycle (ORC) systems which utilizes CO2 and water as geofluids for electricity generation. The simulation was performed using Hysys v11 software by using Peng Robinson’s fluid property package. Two dry working fluids including isopentane and n-pentane, were used. The effects of geofluid temperature and working fluid mass flowrate on power generation, as well as the maximum pressure of working fluids were evaluated.  The result showed that power generation increases with higher geofluid temperature due to enhanced heat transfer. Isopentane outperformed n-pentane, attributed to its superior thermodynamic properties.  CO2 showed better performance as geofluid than water highlighting its superiority, observed in the increased power generation. The unique characteristics of CO2 enable efficient heat transfer at lower temperatures, making it an environmentally friendly and effective choice. Contrarily, the use of water as a geofluid poses some implications for local ecosystems and water resources. From an environmental perspective, CO2 shows greater potential for reduced environmental impact, which aligns with the transition to cleaner energy sources. However, the economic considerations suggest a trade-off, as CO2 projects may entail higher upfront costs compared to water-based systems. Regulatory factors and economic feasibility, therefore, play a crucial role in the choice of geofluid for geothermal power generation.